Jamaah Wadah Nun, Disiplin, Kebebasan dan Amalan: Refleksi dari Penelitian Lapangan - Arfah Lalang (Budapest International Research and Critics University, 2014)
The study of the discipline has been carried out by the experts, one of whom was Foucault, whose his work illustrates the discipline can be formed when a person is bound by rules curbing him/her . He took the example of military institutions or educational institutions as a mode of discipline, that in which there are